Analysis of the Role of CHSE on the Quality of Service of Balkondes around Borobudur Temple to Support the Sustainable Development Goals Program - Irfan Ariyanto Iha; Husna Leila Yusran; Maria Ariesta Utha (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to analyze the effect of CHSE implementation on the Quality of Service of Balkondes around Borobudur Temple, and also to analyze the activities of Balkondes in implementing CHSE so far there are obstacles or not so that researchers know what strategies Balkondes are doing for the sustainability of the SDGs program. This research uses a Mix Method approach, namely using quantitative methods to test the effect of CHSE implementation on service quality, and using qualitative methods to analyze activities, challenges and strategies of balkondes in implementing CHSE so that they can support the SDGs program. The results showed that the application of CHSE has no significant effect on the quality of balkondes services and also balkondes activities provide many benefits to visiting tourists and experience many obstacles in implementing CHSE because many tourists do not comply with the rules imposed by each Balkondes.